A new tigliane-type diterpenoid from Euphorbia tirucalli. Issue 20 (13th October 2022) - Weng, Han-Zhuang; Tian, Yang; Zhang, Jun-Sheng; Huang, Jia-Luo; Tang, Gui-Hua; Yin, Sheng
Abstract: Five tigliane (1 −5 ) and one ingenane (6 ) diterpenoids were isolated from the ethanol extract of Euphorbia tirucalli . The structures of these compounds were identified based on analysis of their spectroscopic data. Among them, compound 12- O -(2 E, 4 E, 6 E, 8 E -tetradecatetraenoyl)-13- O -isobutyroyl-4 β -deoxyphorbol (1 ) was a new tigliane. The Rho123 effluxion assay showed that tiglianes with a trans -fused 5/7 ring system such as compounds 1, 2, and 4 had potent inhibitory activity against P-glycoprotein in HepG2/ADR cells. GRAPHICAL ABSTRACT: UF0001